Effectiveness of Influenza Vaccination in Reducing Subsequent Antibiotic Prescribing in Young Children Attending Australian General Practices—A Case-Control Study. Issue 6 (8th April 2022) - Gianacas, Christopher; Muscatello, David; Blogg, Suzanne; Kirk, Martyn; McIntyre, Peter; Cheng, Allen; Liu, Bette
Abstract: Background: Vaccination against influenza may reduce antibiotic use, but data are limited and imprecise. Methods: We conducted a case-control study using deidentified data from a large national primary care database to evaluate antibiotic prescribing changes following influenza vaccination in children 1-4 years old attending primary care in the Australian 2018 and 2019 influenza seasons. Cases were prescribed β-lactam or macrolide antibiotics during the influenza season and controls were not. Influenza vaccination was documented in the medical records. Adjusted odds ratios for antibiotic prescribing according to influenza vaccination status were estimated using generalized estimating equations, controlling for age, asthma diagnosis, other vaccinations, practice visit frequency, and attendance week. Results: In 2018, 11 282 cases and 32 020 controls were eligible, and in 2019, 12 705 cases and 36 858 controls. Antibiotic prescriptions were less likely in vaccinated participants in 2018 (aOR, 0.65; 95% CI, 0.62-0.69) and 2019 (aOR, 0.78; 95% CI, 0.73-0.82) and did not vary by age, the number of GP visits, or prior prescribing of antibiotics. In the subgroup of children vaccinated in the preceding season, influenza vaccination was not associated with a reduction in antibiotic use (2018—aOR, 1.12; 95% CI, 0.90-1.39; 2019—aOR, 1.30; 95% CI, 1.16-1.46). From our estimates, potentially 100 000 antibiotic prescriptions could be avoided annually in Australia if all children in this age range were vaccinated. Conclusions: Influenza vaccination may substantially reduce antibiotic prescribing among young children. This effect should be considered in the overall assessment of the costs and benefits of childhood influenza vaccination programs. Abstract : A case-control study in more than 40 000 1-4 years old children attending primary care in Australia in each of the 2018 and 2019 influenza seasons found annual influenza vaccination was associated with reduced antibiotic prescribing.